2016
DOI: 10.1002/14651858.cd011281.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous rapid-acting insulin analogues for diabetic ketoacidosis

Abstract: Our review, which provided mainly data on adults, suggests on the basis of mostly low- to very low-quality evidence that there are neither advantages nor disadvantages when comparing the effects of subcutaneous rapid-acting insulin analogues versus intravenous regular insulin for treating mild or moderate DKA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 59 publications
1
38
0
1
Order By: Relevance
“…Analysis of our data showed that severe DKA was correlated with a longer time to resolution, which could be an explanation for the shorter time to resolution observed in the previous study. [21] There are notable differences between our sample and the abovementioned studies: RESEARCH they were performed in developedworld settings, demographics were different, children were included as participants, insulin analogues were sometimes used as opposed to human insulin and patients were mostly managed in an ICU setting. It is, however, not clear whether time to resolution has any impact on improved clinical outcomes; therefore, this cannot necessarily be used to prove efficacy until further studies are performed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of our data showed that severe DKA was correlated with a longer time to resolution, which could be an explanation for the shorter time to resolution observed in the previous study. [21] There are notable differences between our sample and the abovementioned studies: RESEARCH they were performed in developedworld settings, demographics were different, children were included as participants, insulin analogues were sometimes used as opposed to human insulin and patients were mostly managed in an ICU setting. It is, however, not clear whether time to resolution has any impact on improved clinical outcomes; therefore, this cannot necessarily be used to prove efficacy until further studies are performed.…”
Section: Discussionmentioning
confidence: 99%
“…[1820] A Cochrane review evaluating SC bolus IV insulin reported a time to resolution of 11 h in 5 RCTs. [21] This study, however, only evaluated participants with mild to moderate DKA. Analysis of our data showed that severe DKA was correlated with a longer time to resolution, which could be an explanation for the shorter time to resolution observed in the previous study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is no significant difference in outcomes for intravenous regular insulin versus subcutaneous rapid-acting analogs when combined with aggressive fluid management for treating mild or moderate DKA (66). Patients with uncomplicated DKA may sometimes be treated with subcutaneous insulin in the emergency department or step-down units (67), an approach that may be safer and more cost-effective than treatment with intravenous insulin (68).…”
Section: Diabetic Ketoacidosis and Hyperosmolar Hyperglycemic Statementioning
confidence: 99%
“…Пембролізумаб, який використовується для лікування меланоми і пригнічує Т-клітинну відповідь. Він може впливати на нормальну функцію, збільшити активацію Тклітин з наступним ризиком несприятливих автоімунних побічних ефектів, як наприклад, до важкої ендокринопатії, викликаної високими рівнями антитіл до GAD [52]. Справжній наплив публікацій існує про нові випадки кетоацидозу внаслідок застосування нової групи цукрознижуючих препаратів (гліфлазидів), які мають неабиякі переваги в серцево-судинній протекції, ефективно знижують рівень глікемії, проте стають причиною розвитку кетозу-кетоацидозу [53].…”
Section: вступunclassified